Formation of Nuclear Bodies of Arabidopsis CRY2 in Response to Blue Light Is Associated with Its Blue Light–Dependent Degradation - Yu, Xuhong (American Society of Plant Biologists, 2009)
Arabidopsis thaliana cryptochrome 2 (CRY2) mediates photoperiodic promotion of floral initiation and blue light inhibition of hypocotyl elongation. It has been hypothesized that photoexcitation derepresses CRY2 by disengaging its C-terminal domain from the N-terminal PHR domain. To test this hypothesis, we analyzed activities of CRY2 fused to green fluorescent protein (GFP) at either the N terminus (GFP-CRY2) or the C terminus (CRY2-GFP). While GFP-CRY2 exerts light-dependent biochemical and physiological activities similar to those of the endogenous CRY2, CRY2-GFP showed constitutive biochemical and physiological activities. CRY2-GFP is constitutively phosphorylated, it promotes deetiolation in both dark and light, and it activates floral initiation in both long-day and short-day photoperiods. These results are consistent with the hypothesis that photoexcited CRY2 disengages its C-terminal domain from the PHR domain to become active. Surprisingly, we found that CRY2-GFP, but not GFP-CRY2, formed distinct nuclear bodies in response to blue light. Compared with GFP-CRY2 or the endogenous CRY2, CRY2-GFP degradation was significantly retarded in response to blue light, suggesting that the nuclear bodies may result from accumulation of photoexcited CRY2-GFP waiting to be degraded. Consistent with this interpretation, we showed that both GFP-CRY2 and endogenous CRY2 formed nuclear bodies in the presence of the 26S-proteasome inhibitors that block blue light–dependent CRY2 degradation.